Pendidikan karakter, Konsep Dan Aplikasinya Pada Sekolah Berbasis Agama Islam - M. Yusuf (Intizam, Jurnal Manajemen Pendidikan Islam, 2017)
Character education is now a major issue of education. In addition to being part of the process of character building of the nation's children, this character education is also expected to be the main foundation in improving the level and dignity of the Indonesian people. Character formation begins with the nature of God's giving, which is then patterned so that it becomes identity and behavior. In the process itself, this natural disposition is strongly influenced by the state of the environment both the family and the surrounding community, seeing this reality every school and community must have discipline and habits regarding the character to be formed. Leaders and community leaders must also be able to provide an example of the character that will be formed. The concepts and applications planned by Islamic education institutions will provide a very urgent influence. The institution must be able to carry out several principles of developing character education in Islamic-based schools namely sustainability, through all subjects, self-development and school culture, values ​​are not taught but developed, the process of character education is carried out actively by students. Thus the development of character education can be through subjects (integrated), self-development activities and school culture.